PERUBAHAN MORFOLOGI DAN KIMIA BATUAN PEMBAWA FOSFAT AKIBAT PELINDIAN DENGAN ASPERGILLUS NIGER - TATANG WAHYUDI (Puslitbang tekMIRA, 2009)
Bioleaching, utilizing oxalic acid medium generated by the phosphorous oxidizing capabilities of Aspergillus niger in 10 days, has proved to be useful in releasing phosphorous from its rocks. In terms of evaluating process performance, microscopic and chemical studies were conducted to bioleaching. The results show several features occur during the process. Porosity and permeability developments on the surface of dahlite and calcite during bioleaching process imply that the process is effective to leach such minerals. Both are competent agents for leaching solution to contact with the required elements available within the minerals. The detected pits on the mineral surface reflect solution activity when leached the materials.